Estrategias de evaluación y resultados de aprendizaje - Calderon Caiza, Daysi Tatiana (2018)
Current education requires quality processes, whose actions orient student´s academic activities. From this perspective the educational actors must generate changes in the ways of evaluating the students, it becomes integral and attend to the needs of each one of them. Teachers should promote active teaching and learning strategies, which are the basis for determining evaluation strategies. The lack of diversification in the application of evaluation strategies makes it difficult to verify the learning achievements, which causes that no decision can be made about the learning and academic performance at the right time, through processes of feedback. The objective of this research is to analyze the evaluation strategies by means of the characterization of their components to determine the learning outcomes achieved in the pedagogical process. The applied research methodology is based on the quantitative approach; the deductive-inductive methods were used, as well as the bibliographical and field research to describe the evaluation strategies and the learning outcomes. The techniques used were the interview and the survey, with their respective instruments the interview guide and the questionnaire, which allowed gathering information to authorities, teachers and students about the problems studied. The results found made it possible to determine that teachers apply traditional evaluation strategies due to ignorance of strategies, techniques and evaluation instruments, which have generated monotony in the evaluation process and reflected in the learning outcomes achieved. This research contributes significantly in the educational field, because it provides teachers with theoretical information on evaluation strategies and learning outcomes, through planning processes, information gathering, and issuance of value judgments, results socialization and decision-making, aimed at achieving a comprehensive training of students